Low to very high temperature thermal energy recycling – 3 case studies - Høeg Arne (EDP Sciences, 2021)
In this paper we present three case studies of the installation of a stirling-cycle high temperature heat pump applied to recycling thermal energy including steam generation. Many industries have heat demand at temperatures above 100°C and often the preferred energy carrier is steam. The optimal integration of a heat pump can be determined by investigating the thermal need of the process with pinch technology. For many industries, the pinch temperature is too high for conventional heat pumps. We present a heat pump solution that can recycle thermal energy and deliver this to a heat source up to 200°C, as hot water or steam. The heat pump can be integrated in a thermodynamic efficient way placing the sink and source in-between the pinch temperature. The working medium is a gas throughout the process cycle, with no evaporation or condensation. Thus, the process can auto-adjust to temperature variations and achieve very high efficiencies compared to the Carnot heat pump cycle. The coefficient of performance (COP) of the heat pump vary with the sink/source temperatures as the temperature fraction varies. Another important feature is that the medium has both a global warming potential (GWP) and ozone depletion potential (ODP) of zero. The thermodynamics of the heat pump is explained in more detail in the introduction section. The first installation is at a dairy plant on the west coast of Norway. In this installation, the heat pump provides cooling at 0-5°C and converts this heat into hot water at 120°C. The second installation is also at a dairy in Norway. Here the heat pump cools the ammonia from the cooling compressors at about 25-30°C and converts the heat to hot water at 110C°. The third installation is at a beverage plant on the west coast of Norway. Here the heat pump is providing cooling to compressors and other equipment. The final temperature of the heat source varies from 20-70°C. The heat is converted into steam at 168°C. In the case study sections, the installations are discussed in more details, together with the performance and a discussion of the experiences with the technology.